GE_GERICHTE C/19956/2012 vom 13. September 2013 - GE Cour de justice (2013)
CONTRAT D'ASSURANCE; INTERPRÉTATION(SENS GÉNÉRAL); CONDITIONS GÉNÉRALES DU CONTRAT | CO.18; CPC.95.3.A; CPC.95.3.C; CPC.105.2; CPC.151; CPC.316.3